The Influence of Empowerment Leadership on Intrinsic Motivation of Employees in The Environmental Services Binjai City Living - Rukun, Rukun; Sugiarto, Abdi (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
The purpose of this research is to determine and analyze the influence of empowerment leadership on intrinsic motivation in the Binjai City Environmental Service. This research was conducted using a causal associative quantitative approach. The sample used was all employees with a total of 75 people taken using proportional sampling. The research results show that empowering leadership has a positive and significant effect on intrinsic motivation. This is shown by the T-count value of T-count of 9.919 > t table 1.6666, with a significance value of 0.000 < 0.05. The regression coefficient shows that if empowerment leadership is increased by 1 unit, then intrinsic motivation will increase by 0.364 units. assuming other variables remain constant. Apart from that, the results of the determination test show an Adjusted R Square value of 0.568 or 56.80%, which indicates that empowerment leadership has a low influence on intrinsic motivation, while the remaining 43.20% is influenced by other factors that have not been studied. Thus, partially, empowering leadership has a positive and significant effect on the work of employees at the Binjai City Environmental Service. This identifies that meaning, improvements in empowering leadership can contribute to increased intrinsic motivation.